An assessment of emergency and disaster preparedness in high schools in Istanbul-Turkey - (:unkn) unknown (DRUNPP-SARAJEVO, 2012)
This study was carried out as a descriptive study; to determine the most probable hazards/emergencies in high schools in Istanbul and; to evaluate the preparedness for disasters and emergencies and; to find out the differences between school types in regards to disaster and emergency preparedness. The research was conducted with 2500 school employees and administrators working in 150 public and private high schools in Istanbul. Data were collected through A Questionnaire Form for Emergency and Disaster Preparedness in Schools, developed by the researcher of this study. While Public High Schools covered in the study were found to be unprepared for disasters and emergencies, Private Turkish High Schools were found to be more prepared for disasters and emergencies than the other school types. Findings show that students and employees working in schools, and school buildings and education will be negatively affected in a probable major disaster/emergency situation in Istanbul.
Keywords: Emergency; Disaster Preparedness; High School